please give solution as fast as possible with solution without giving nonsense ideas
Attachments:
![](https://hi-static.z-dn.net/files/dce/c87cb946f5da9ed59170ba418f8dc9ae.jpg)
Answers
Answered by
1
Question:
Solution:
We know that,
90° - 63° = 27°
90° - 27° = 63°
90° - 17° = 73°
90° - 73° = 17°
Also,
sinθ = cos(90° - θ)
cosθ = sin(90° - θ)
Using sin(90° - θ) = cosθ and cos(90° - θ) = sinθ we get,
We know that sin²θ + cos²θ = 1
Applying it above we get,
Therefore,
Answered by
0
Chandu r u there now???? hello hey.....h r u ??
r u okay?
Similar questions
English,
6 months ago
English,
6 months ago
Math,
1 year ago
Business Studies,
1 year ago
Geography,
1 year ago